Improving Students’ Vocabulary Through Unjumbled Word Wall Medium at Grade Seven of SMPN 1 Parongpong - Ayu Winda Marpaung; Caroline V Katemba (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the effectiveness of using the Unjumble Word Wall media in improving students’ vocabulary mastery in English language learning. A quantitative experimental design was employed by administering pre-tests and post-tests to seventh-grade students at SMPN 1 Parongpong, West Java. The experimental group received vocabulary instruction using the Unjumble Word Wall application, while the control group was taught using the standard Word Wall media. The collected data were analyzed using descriptive statistics, normality tests, N-Gain analysis, and paired sample t-tests. The results indicate a significant improvement in vocabulary mastery among students who used the Unjumble Word Wall media. The post-test mean score (M = 89.77) was substantially higher than the pre-test mean score (M = 48.37), demonstrating the effectiveness of the Unjumble feature in enhancing students’ vocabulary learning. The N-Gain percentage (78.77%), categorized as high, further confirms the strong impact of the media. Despite these positive outcomes, several challenges were noted, including students’ varying digital literacy and limited internet access during learning sessions. In conclusion, integrating the Unjumble Word Wall media into English vocabulary instruction provides an effective, engaging, and interactive learning experience that enhances students’ vocabulary mastery and participation in class activities.